The Formulation Policy of the Murder with Mutilations Crime - Diah Ratu Sari Harahap (Budapest International Research and Critics University, 2022)
The type of murder committed by mutilation is a vicious crime. However, this type of crime has not been expressly regulated in the Criminal Code, so there are no guidelines for prosecutors in preparing charges against this type of crime. As a result, the decisions handed down by judges are also varied and sometimes do not fulfil a sense of justice. This study aims to reveal the regulation of murder with mutilation in Indonesian positive criminal law and to determine the future policy formulation regarding the crime of murder with mutilation. The research is normative by conducting a literature study. The data that has been obtained were analyzed qualitatively by describing. This research hopes that a particular article will be made in the Criminal Code regarding murder accompanied by mutilation.